INTERPRETATION OF GENRE AND PERSONAL CHARACTERISTICS IN MODERN STORYTELLING - Shukurova Bahor Boltayevna (Western European Studies, 2024)
The development of the literary and artistic process, the entering of the art of speech into a new era, shows that certain changes are taking place in the structure of the story in terms of form and content. Such a phenomenon is manifested, including, in Uzbek prose. Such evolutions are visible not only in the story, but also in the artistic device of the novel, which is considered a large epic form. Through the study of some stories, the article talks about the traditional features of the artistic-poetic world of the story, as well as its updates
Keywords: Story; epic type; expansion of the chronotope; brevity in the story